(untitled) (Revista Rupturas, 2025)
This article explores the Indigenous, territorial and community feminism practices of “Territorias cuidando y sosteniendo la vida” a movement led by the Consejo Regional Indígena y Popular de Xpujil (CRIPX) in Calakmul, Campeche, southeast Mexico. Through a collaborative ethnographic study, we examine the role of reclaiming spaces, practices and knowledge in traditional medicine and healing, which serve as pillars of the collective care of the women of CRIPX in response to the various forms violence they face daily. By politicizing their wounds and painful experiences, these women challenge and transform their micro-social spaces including the domestic, community and organizational realms. This process fosters new ways of inhabiting and understanding the world through collective care.